2001
DOI: 10.7863/jum.2001.20.8.821
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic and Doppler characteristics of the corpus luteum: can they predict pregnancy outcome?

Abstract: Objective. To determine whether there is a relationship between gray scale or Doppler characteristics of the corpus luteum and first-trimester pregnancy outcome. Methods. We conducted a prospective study of patients with spontaneous singleton pregnancies between 5 and 8 weeks' gestation. The corpus luteum size, sonographic appearance, resistive index, and peak systolic velocity were measured on transvaginal sonography. Maternal use of exogeneous progesterone was recorded. Only patients with known first-trimest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
2
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 11 publications
3
18
2
2
Order By: Relevance
“…This finding was in disagreement with previous studies T A B L E 3 Biochemical markers and uterine artery resistance index represented as a percentage of the normal standard level at a given pregnancy duration. 15 The uterine artery Doppler indices were not significantly different between the groups in the present study. that assessed the embryonic heart rate very early in pregnancy (at 6 weeks) and found that a slow heart rate (less than 110 beats/min) was associated with fetal demise.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This finding was in disagreement with previous studies T A B L E 3 Biochemical markers and uterine artery resistance index represented as a percentage of the normal standard level at a given pregnancy duration. 15 The uterine artery Doppler indices were not significantly different between the groups in the present study. that assessed the embryonic heart rate very early in pregnancy (at 6 weeks) and found that a slow heart rate (less than 110 beats/min) was associated with fetal demise.…”
Section: Discussioncontrasting
confidence: 58%
“…15 To eliminate inter-observer variability, the Doppler examinations were performed by a single sonographer (HAAA). After identifying the uterine artery waveform, at least three consecutive correctly imaged waveforms were assessed by pulsed Doppler.…”
Section: Methodsmentioning
confidence: 99%
“…365 Claims have been made that correlations exist between CL Doppler data and quality of the luteal phase, 366 leading to the proposal that Doppler data could be used for assessing the luteal phase 367 and predicting pregnancy outcome. 368 In spontaneously occurring singleton pregnancies, Frates and colleagues failed to find a correlation between the echographic characteristics of the CL and first trimester pregnancy outcome. 368 On gray-scale images, we believe that an educated eye can easily identify the fine dual contours of vessels that run around the CL, an impression which is supported by the finding of a correlation between Doppler data and vascular density.…”
Section: Perfusion Of the Maturing Follicle And Corpus Luteum (Cl)mentioning
confidence: 96%
“…368 In spontaneously occurring singleton pregnancies, Frates and colleagues failed to find a correlation between the echographic characteristics of the CL and first trimester pregnancy outcome. 368 On gray-scale images, we believe that an educated eye can easily identify the fine dual contours of vessels that run around the CL, an impression which is supported by the finding of a correlation between Doppler data and vascular density. 369 It should be noted that the increased vascularity of the CL may at times be confused with the vascular ring that characterizes certain ectopic pregnancies.…”
Section: Perfusion Of the Maturing Follicle And Corpus Luteum (Cl)mentioning
confidence: 96%
“…Ayırıcı tanı geniş olup şüpheli durumlarda ektopik gebeliğin US ile dışlanması gerekir. US'de ön planda korpus luteumdan ayrılması gerekli olup korpus luteumun intraadneksal kist ya da kitle şeklinde görülmesi ayrımda önemlidir [22].…”
Section: Ektopik Gebelikunclassified